Evaluating mobile collaborative applications support of teamwork in critical incidents response management - Sapateiro, Cláudio Miguel Garcia Loureiro dos Santos (2013)
Tese de doutoramento, Informática (Engenharia Informática), Universidade de Lisboa, Faculdade de Ciências, 2013